Selves as solutions to social inequalities : why engaging the full complexity of social identities is critical to addressing disparities - Brannon, Tiffany N; Fisher, Peter H.; Greydanus, Abigail J. (Cambridge : Cambridge university press, 2020)
Social disparities linked to social group membership are widespread and persistent within mainstream institutions (e.g., schools, workplaces). In response, psychological science has focused on the concept of the self, which is flexible and significantly influenced by social group membership, as a means to address inequality. We propose and review evidence suggesting that the theoretical and practical effects of using the 'self as a solution' can be enhanced through a stigma and strengths framework. This framework views the self in its full complexity, recognizing that the same social group membership can be associated with both stigma, risk, and devaluation, as well as strengths, resilience, and pride. We present evidence that by implementing policies and practices that (a) reduce stigma and (b) acknowledge and include strengths, mainstream institutions can more effectively reduce social disparities related to inclusion, achievement, and well-being. By examining social groups with varying status and power, we explore the implications of this framework, including its potential to promote positive, recursive, and intergroup effects on social inequalities.
1. Overview; 2. Background: Motivating the Current Framework; 3. Current Framework: Towards a Stigma and Strengths Approach; 4. Resistance to Stigma can Foster Strengths (Pride) Among LGBTQ+ Individuals; 5. Making the Invisible Visible: Examining Dominant Group Identities in Context; 6. Closing Discussion.
Includes bibliographical references
Keywords: Equality - Psychological aspects; Identity (Psychology) - Social aspects; Social psychology